Empowering Student’s Activity with ICT: Case of Weekly Discussion in University of Darussalam - Taqiyuddin, Muhammad; Yudhistira, Bagus; Fadillah, Rizki Maulana (Proceeding International Conference on Science and Engineering, 2021)
Abstract. In the Covid-19 era, almost everything was done online. Likewise student discussion activities. At Darussalam University, all students are required to take part in weekly discussions. That is supervised by semester 7 with supervision from the presenters lecturer. This field research collected data on students' weekly discussions, as well as techniques in improving the quality of their literacy. This study resulted in the finding that discussion management can be carried out using an online system. The platform used is Google. Especially drives and email. Google Drive is used as a material bank and discussion reference along with the schedule of the presenters. Google Forms is used for monitoring absent activities and documentation.